Association between neuropeptide Y receptor Y2 promoter variant rs6857715 and major depressive disorder. (February 2017) - Treutlein, Jens; Strohmaier, Jana; Frank, Josef; Witt, Stephanie H.; Rietschel, Liz; Forstner, Andreas J.; Lang, Maren; Degenhardt, Franziska; Dukal, Helene; Herms, Stefan; Streit, Fabian; Hoffmann, Per; et al.
Abstract : Stress increases the risk for major depressive disorder (MDD), overeating, and alcohol dependence (AD). The neuropeptide Y system is one of the best-known modulators of the stress response, and some of its effects are mediated through the neuropeptide Y receptor Y2 ( NPY2R ). The functional NPY2R variant rs6857715 (C-599T) has been implicated in both obesity and AD, but with opposing alleles. The present study explored whether rs6857715 is also associated with MDD. Analysis of the overall sample (595 MDD cases; 1295 controls) showed an association with the AD risk allele C [ P =0.020, odds ratio (OR) (C-allele)=1.18]. The association remained significant after excluding MDD patients with AD/alcohol abuse [ P =0.038, OR (C-allele)=1.18]; increased weight/appetite [ P =0.006, OR (C-allele)=1.23]; or both [ P =0.008, OR (C-allele)=1.25]. The present findings suggest that the NPY2R rs6857715 C-allele makes a genuine contribution toward MDD. Abstract : Supplemental Digital Content is available in the text.